Managerial Accountability of Madrasah Principals and Teacher Performance of Private Madrasah Aliyah in Banten Province - Wawan Abdullah; Encep Syarifudin; Nafan Tarihoran; Rijal Firdaos; Supardi Supardi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study explores the influence of managerial accountability of madrasah principals on teacher performance in private Madrasah Aliyah in Banten Province, Indonesia. As demands for quality Islamic education increase, the role of principals in ensuring transparent, responsible, and effective management becomes crucial. Using a quantitative explanatory design, data were collected from 217 teachers across 28 madrasahs through stratified random sampling. Due to non-normal data distribution, Spearman’s Rho correlation was used for analysis. The results show that managerial accountability and teacher performance fall into the “good” category. The highest accountability dimension was responsibility, while personality was the strongest teacher performance aspect. A moderate positive correlation (r = 0.526, p < 0.01) was found between principals’ managerial accountability and teacher performance, with 27.6% of the performance variance explained by the accountability factor. Among the dimensions, responsibility had the strongest impact, followed by control, transparency, and responsiveness. This study highlights the importance of strengthening accountability practices among madrasah principals to improve teacher performance and educational outcomes. The findings provide valuable insights for policymakers and Islamic education leaders to promote effective, value-based school governance.